Mapping Teacher Competency in Islamic Education: A Systematic Literature Review and Future Research Agenda - Triono Ali Mustofa; Nurul Latifatul Inayati; Lina Agustina; Ima Aryani; Viky Nur Vambudi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to map the development of teacher competency studies in Islamic education, identify the main dimensions and competency models used, and formulate future research agendas. This study uses the Systematic Literature Review (SLR) method with the PRISMA flow. Data was obtained from the Scopus database through a selection of empirical articles in English, open access, subject area Arts and Humanities, and published in the 2023–2026 period. Of the initial 93 articles, 24 articles met the inclusion criteria and were analyzed descriptively and thematically. The results of the study show that the competency study of Islamic education teachers will develop significantly, especially in 2024–2025, with the dominance of the Indonesian locus and expansion to several Asian and European countries. Methodologically, studies are still dominated by qualitative approaches, although more complex quantitative methods, mixed-methods, R&D, and statistical analysis are emerging. Conceptually, the competence of Islamic education teachers shifts from pedagogic and professional competencies to multidimensional concepts that include digital, spiritual, ethical, social, leadership, curriculum innovation, and integration of Islamic values. This research concludes that future research needs to develop a more comprehensive, measurable, cross-contextual, and relevant model of Islamic education teachers to the transformation of education in the 21st century.